2020
DOI: 10.1038/s41598-020-57793-2
|View full text |Cite
|
Sign up to set email alerts
|

The plant natural product 2-methoxy-1,4-naphthoquinone stimulates therapeutic neural repair properties of olfactory ensheathing cells

Abstract: Olfactory ensheathing cells (OECs) are crucial for promoting the regeneration of the primary olfactory nervous system that occurs throughout life. Transplantation of OECs has emerged as a promising therapy for nervous system injuries, in particular for spinal cord injury repair. Functional outcomes in both animals and humans are, however, highly variable, primarily because it is difficult to rapidly obtain enough OECs for transplantation. Compounds which can stimulate OEC proliferation without changing the phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…These compounds have been found to exhibit antibacterial, antifungal, antioxidant, hepatoprotective, cardioprotective, anti-ischaemic properties and other properties. Their role in protecting against neurodegenerative diseases such as Alzheimer’s disease (AD) and Parkinson’s disease has also been established [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. One of the 1,4-NQs synthesized by our group, U-133, exhibited a promising neuroprotective effect in an in vivo PD rat model [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds have been found to exhibit antibacterial, antifungal, antioxidant, hepatoprotective, cardioprotective, anti-ischaemic properties and other properties. Their role in protecting against neurodegenerative diseases such as Alzheimer’s disease (AD) and Parkinson’s disease has also been established [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. One of the 1,4-NQs synthesized by our group, U-133, exhibited a promising neuroprotective effect in an in vivo PD rat model [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The capacity for phagocytosis by transplanted OECs is also likely beneficial, as the cells can help clear cell debris present at the injury site. Compounds that can stimulate the phagocytic activity of OECs without causing a strong pro-inflammatory response have been suggested to potentially increase the therapeutic potential of these cells 64 68 . Thus, it is important to characterise which cytokines are expressed by OECs under various conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have to date identified compounds that can stimulate OEC phagocytosis (as well as autophagy -a topic which remains to be studied in itself). We, along with laboratories around the world, have identified various agents that can increase OEC phagocytosis, including the natural products 2-methoxy-1,4-naphthoquinone (Chen et al, 2020), the serrulatane diterpenoids 3-acetoxy-7,8-dihydroxyserrulat-14-en-19-oic acid and 3,7,8-trihydroxyserrulat-14-en-19-oic acid (Chen et al, 2018), curcumin (Velasquez et al, 2014); curcumin in combination with E. coli-derived LPS (Hao et al, 2017), and anti-inflammatory cytokine TGF-β (Li et al, 2017). In vitro injury assays (neurons co-cultured with OECs accompanied by neuronal debris addition), showed that increased OEC clearance of debris due to application of stimuli (LPS + curcumin Hao et al, 2017or TGF-β Li et al, 2017 promoted neuronal survival.…”
Section: Stimulating Phagocytosis Of Peripheral Glia To Treat Neural Injuriesmentioning
confidence: 99%